Book Review: Network Analysis and Tourism – From Theory to Practice by Noel Scott, Rodolfo Baggio and Chris Cooper. (29th September 2009) - Tremblay, Pascal
Network Analysis and Tourism – From Theory to Practice, by Noel Scott, Rodolfo Baggio and Chris Cooper. Clevedon, UK, Channel View Publications, 2008. ISBN-13: 978-1-84541-088-9 (hbk); ISBN-13: 978-1-84541-087-2 (pbk)